Islamic banks in Algeria in light of current and future challenges - Hamidi, Keltoum; Imane, Hayoula; Kheira, Daoud (The International tax journal, 2026)
Islamic financial institutions in Algeria are a current development that has established itself on the economic and financial scene, both as a global economic and financial phenomenon and as a tool of Islamic finance through which the state seeks to strengthen its economic policies by achieving economic growth and development. Islamic banks have received significant and growing attention from researchers and economic writers, particularly in Arab and Islamic countries, which have found solutions to their economic and social problems. Islamic banks have come to rely on interest-free credit activities and offer a new credit activity that transcends the traditional roles of Islamic banks (murabaha, musharakah, mudaraba). This has created new economic and financial challenges for achieving economic growth and development, one way or another, by exploiting savings to directly finance investments. This has created an economic environment that is compatible with the nature of the economies of Arab and Islamic countries, even developing ones, and in line with the nature of Islamic customs, traditions, and values.